The Visigoths in Gaul and Iberia (update) : a supplemental bibliography, 2004-2006 - Ferreiro, Alberto (Medieval and early modern Iberian world, 2008)
Includes material published from 2004 to 2006. This volume covers literature on: Archaeology, Liturgy, Monasticism, Iberian-Gallic Patristics, Paleography, Linguistics, and Germanic and Muslim Invasions. It includes peoples such as the Vandals, Sueves, Basques, Alans and Byzantines.